Effect of Alkaline and Acid Phosphatases on Clotting: - Iatridis, P. G; Ferguson, J. H (Thrombosis and Haemostasis, 1966)
Alkaline phosphatase is found to enhance the activation of factor IX by SF. The correlation of the distribution of alkaline phosphatase in electrophoretic fractions with the clotting tests suggest that the “beta” fraction contains the responsible factor for the acceleratory effect of alkaline phosphatase on clotting.Acid phosphatase, while not exerting a direct inhibitory effect on SF, does enhance the plasmatic anti-SF activity. The “beta” and “F-gamma” fractions seem to contain the responsible factor of acid phosphatase for the plasmatic anti-SF enhancement.SF preparation has no acid or alkaline phosphatase activity.A tentative schema is proposed to explain the effects of acid and alkaline phosphatase on clotting.